An automated drip irrigation system based on soil electrical conductivity - Yildiz, Abdunnasir (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
We assessed the irrigation performance of the automated irrigation controller. In the study, a drip irrigation system automatically governed irrigation in accordance with water consumption of the substrate-plant system. Data acquisition was performed by an electronic circuit, which processed data and then sent the data to the microcontroller (programmable integrated circuit-pic16f84). The pic16f84 functioned as a controller, which decided when and how much water to apply; hence, the pumps ran and stopped according to the irrigation strategy defined by the microcontroller. The required time to pump water according to the irrigation programs corresponded to the time to increase soil moisture up to field capacity in the full treatment whenever 30% of the available water in the substrate was depleted by the pepper plant (Capsicum annuum L.) in the experiment. Therefore, once defined, the microcontroller utilized the data and controlled the relays connected to the pumps. Soil moisture content was monitored by only one sensor installed in a representative pot throughout the experiment. The automated system applied four different water applications; one treatment was full and the other three were deficit treatments. These were compared with the control treatment. The automated system maintained the soil moisture level at the desired level for the full treatment and took over irrigation events, started and stopped the irrigations throughout the entire growing season. Even though yield value was high in treatment I 1.0 , the best quality parameters were obtained from I 0.75. In the deficit treatments I 0.50 and I 0.25 , yield and quality parameters decreased since plants in those treatments were under stress. The performance of the automated system can be increased as the time in the software is adjusted according to full irrigation application.